2010
DOI: 10.1107/s1600536810015795
|View full text |Cite
|
Sign up to set email alerts
|

3,5-Bis(4-bromophenyl)-1-phenyl-4,5-dihydro-1H-pyrazole

Abstract: In the title compound, C21H16Br2N2, the central pyrazole ring adopts an flattened envelope conformation, with the stereogenic C atom in the flap position. The deviations from planarity for this ring are relatively minor (r.m.s. deviation = 0.045 Å) and the dihedral angles formed with the N- and Cimine-bound benzene rings are 7.73 (13) and 11.00 (13)°, respectively. By contrast, the benzene ring bound at the chiral C atom is almost orthogonal to the rest of the mol­ecule; the dihedral angle formed between this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…For background to pyrazoline derivatives, see: Fun et al (2010); Samshuddin et al (2010Samshuddin et al ( , 2011. For a related structure, see: Samshuddin et al (2010).…”
Section: Related Literaturementioning
confidence: 98%
See 2 more Smart Citations
“…For background to pyrazoline derivatives, see: Fun et al (2010); Samshuddin et al (2010Samshuddin et al ( , 2011. For a related structure, see: Samshuddin et al (2010).…”
Section: Related Literaturementioning
confidence: 98%
“…Data collection: APEX2 (Bruker, 2009); cell refinement: SAINT (Bruker, 2009); data reduction: SAINT; program(s) used to solve structure: SHELXTL (Sheldrick, 2008); program(s) used to refine structure: SHELXTL; molecular graphics: SHELXTL; software used to prepare material for publication: SHELXTL and PLATON (Spek, 2009 In continuation of our work on synthesis of pyrazoline derivatives (Fun et al, 2010;Samshuddin et al, 2010Samshuddin et al, , 2011, the title compound was prepared and its crystal structure is now reported.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For the synthesis of chalcone derivatives, see: Samshuddin et al (2010;Fun et al (2010); Jasinski et al (2010); Baktır et al (2011). For related structures, see: Fun et al (2011);Jasinski et al (2011).…”
Section: Related Literaturementioning
confidence: 99%
“…Thus, for example, the cyclocondensation reactions of chalcones with simple hydrazines lead to the formation of dihydropyrazole derivatives (Fun et al, 2010;Jasinski, Guild et al, 2010;Jasinski, Pek et al, 2010;Samshuddin et al, 2010). Following these precedents, we have now prepared the title dihydropyrimidine derivative (4RS)-2-amino-4-(6-methoxynaphthalen-2-yl)-6-(pyridin-3-yl)-3,4-dihydropyrimidine monohydrate, (II) (Fig.…”
Section: Introductionmentioning
confidence: 97%